Exophthalmos and multinodular goitre, an unusual combination. (3rd May 2019) - Okolie, Kingsley; Chen, Daniel; Ghabrial, Raf; Schmidli, Robert
Summary: Multinodular goitre is not associated with eye disease, unless in a rare case of Marine–Lenhart syndrome where it coexists with Grave's disease. Therefore, other causes of exophthalmos need to be ruled out when the eye disease is seen in a patient with multinodular goitre. Confusion can arise in patients with features suggestive of Graves' ophthalmopathy in the absence of thyroid-stimulating hormone receptor autoantibodies and no evidence of other causes of exophthalmos. We present a case of multinodular goitre in a patient with exophthalmos which flared up after iodine contrast-based study. A 61-year-old Australian presented with a pre-syncopal attack and was diagnosed with toxic multinodular goitre. At the same time of investigations, to diagnose the possible cause of the pre-syncopal attack, computerised tomographic (CT) coronary artery angiogram was requested by a cardiologist. A few days after the iodine contrast-based imaging test was performed, he developed severe eye symptoms, with signs suggestive of Graves' orbitopathy. MRI of the orbit revealed features of the disease. Although he had pre-existing eye symptoms, they were not classical of thyroid eye disease. He eventually had orbital decompressive surgery. This case poses a diagnostic dilemma of a possible Graves' orbitopathy in a patient with multinodular goitre. Learning points: Graves' orbitopathy can occur in a patient with normal autothyroid antibodies. The absence of the thyroid antibodies does not rule out the disease in all cases. Graves' orbitopathy can coexist with multinodular goitre. Iodine-based compounds, in any form, can trigger severe symptoms, on the background of Graves' eye disease.